ACADEMICIANS URGED TO TRANSFORM AND TO FOCUS ON BEING MORE STUDENT-CENTERED - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 16 December 2016 In the 21st century, challenges facing the future of higher education would be in the offering of flexible education, and in collegiality and commonality in order to move from the local to the global context.